Formulation of lubricating grease from waste oil: A review - Nur Amira Fatihah, Bashari; Mohd Aizudin, Abd Aziz; Muhammad Auni, Hairunnaja; Mohd Azmir, Arifin (Universiti Putra Malaysia, 2024)
This paper demonstrates the potential of waste turbine oil (WTBO) as a base oil to substitute for mineral oil, which is usually used in grease formulations. This study will analyze the characteristics of used turbine oil, including its chemical composition and physical characteristics, including kinematic viscosity, viscosity index, moisture content, contamination, and density. The presence of antioxidants (butylated hydroxytoluene (BHT) and amine or phenyl-a-naphthylamine (PANA), anti-wear, and corrosion-inhibiting additives that can improve the formulated lubricating grease performance and lengthen service life are just a few of the useful remaining WTBO characteristics that can be used wisely as the base oil. It is crucial to create more environmentally friendly, economically sensible, and thrifty grease formulations to adhere to Malaysia’s Green Technology Master Plan, which has outlined the strategic plans for developing green technologies. The new inventions must establish a resource- and carbon- efficient economy. The abundance of WTBO in the aviation industry and the unique characteristics of WTBO itself promise a reliable supply of base oil for lubricating grease in the future.